Code quality assessment tool (CQAT) - Pang, Samuel Shao Xuan (2018)
Software quality assurance is fundamentally different from the software code quality assessment. This is important in evaluating the quality of the undergraduate projects. Current students are only graded on the assignments by the functionality as stipulated in their assignments and their grades are not affected by the code quality attributes that he or she might be lacking in. There might be situations where a student, who just completes the assignment according to the requirements of the assignment, would be given the same grade as a student who goes the extra mile and optimize his code for it to run more efficiently. However, current software metrics and tools are only placing emphasis on the enterprise level software. Furthermore, such tools do not provide means to able to critically evaluate the undergraduate projects. Hence there is a need to develop a code quality tool which will be able to measure and evaluate the source code quality of undergraduate projects. This tool will use novel algorithms and a set of code quality metrics that to specifically assess the quality of undergraduate projects. A code quality report and a rating system will be incorporated. The generated report will also identify specific areas where inefficient coding is present.